Construindo a docência com a flauta doce: o pensamento de professores de música - Souza, Zelmielen Adornes de (2012)
This master thesis was developed within the Line of Research Education and Arts (LR4) from the Postgraduate Program in Education at Federal University of Santa Maria (UFSM) and is part of the research group FAPEM Formation, Action and Research in Musical Education of UFSM. The research had as overall objective to investigate the thinking of four music teachers, graduates from the Music Major Teaching degree of UFSM, in the constitution process of teaching with the recorder. As specific objectives, the study aimed at knowing what the music teachers think about the recorder teaching; understanding the meaning of this musical instrument in their lives and in their teaching practice; and reflecting upon the recorder teaching in the field of musical education. In order to do that, the theoretical framework was based on studies about teacher s thinking (PACHECO, 1995; BRAZ, 2006, 2007; MARUJO, 2004; BEINEKE, 2000; DEL BEN, 2001; among others) which allowed us to reflect upon the meanings and connections among thinking, memory and narrative in the interrelation between the teacher s thinking and doing towards the recorder. Metodologically, the research was held by the thematic oral history method (MEIHY, 2005; FREITAS, 2006), making use of procedures of data production and analysis, respectively, narrative interview (JOVCHELOVITCH; BAUER, 2008) and some strategies of grounded theory (CHARMAZ, 2009). Though this investigation, we were able to know the music teachers histories and their thinking, represented by some of their constructs, ideas, beliefs, knowledge, values, perspectives, etc., which are expressed in their memories-references (JOSSO, 2010) to teach the recorder. In this process, we realized that their thoughts are connected to ratio-affective factors (BAGGIO; OLIVEIRA, 2008) that permeate their experiences with this musical instrument in different moments of their lives, as both music students and teachers, who advance in and give meanings to their current pedagogic-musical practices. Finally, we have understood that these teacher s thinking, about the recorder teaching, constitutes an important dimension in each teacher s formative process, affecting and constituting them, because only in the relation between thinking and doing these professionals learn how to be music teachers with the recorder.